Life Cycle Effect on Firm Capital Structure: Evidence from Jordan - Abd Al-Lateif, Yazeid; AL-Debi'e, Mamoun (Jordan Journal of Business Administration, 2019)
This study aims to examine the effect of firm's life cycle on its capital structure in a sample of (56) industrial companies listed in Amman Stock Exchange (ASE) during the period (2015-2016). The study applied the Dickinson approach (2011) to determine the stages in the firm life cycle. Multiple regression analysis was used to achieve the objectives of the study and test its hypotheses. The results show that the average leverage ratio (Lev) for industrial firms is low. However, the degree of reliance on debt in the capital structure is highest in the introduction and growth stages. Furthermore, regression analysis shows a statistically significant inverse relationship between firm's life cycle stages and the degree of financial leverage in the Jordanian industrial sector, which indicates a gradual development in the explanatory variables across the stages of firm's life cycle. The pecking order theory is the most capable theory to explaining the funding behavior in Jordanian industrial firms throughout all life cycle stages except for the decline stage. Finally, the pecking order theory and trade-off theory in financial management are unable to explain the funding behavior of Jordanian industrial firms in the decline stage.